Contrasting views on co-management of indigenous natural and cultural heritage – Case of Laponia World Heritage site, Sweden - Stjernström, Olof Andreas; Pashkevich, Albina; Avango, Dag (Polar Record, 2020)
publishedVersion Unit License Agreement